Effects of microbial enzymes on starch and hemicellulose degradation in total mixed ration silages - Tingting Ning (Asian-Australasian Journal of Animal Sciences, 2017)
Objective This study investigated the association of enzyme-producing microbes and their enzymes with starch and hemicellulose degradation during fermentation of total mixed ration (TMR) silage. Methods The TMRs were prepared with soybean curd residue, alfalfa hay (ATMR) or Leymus chinensis hay (LTMR), corn meal, soybean meal, vitamin-mineral supplements, and salt at a ratio of 25:40:30:4:0.5:0.5 on a dry matter basis. Laboratory-scale bag silos were randomly opened after 1, 3, 7, 14, 28, and 56 days of ensiling and subjected to analyses of fermentation quality, carbohydrates loss, microbial amylase and hemicellulase activities, succession of dominant amylolytic or hemicellulolytic microbes, and their microbial and enzymatic properties. Results Both ATMR and LTMR silages were well preserved, with low pH and high lactic acid concentrations. In addition to the substantial loss of water soluble carbohydrates, loss of starch and hemicellulose was also observed in both TMR silages with prolonged ensiling. The microbial amylase activity remained detectable throughout the ensiling in both TMR silages, whereas the microbial hemicellulase activity progressively decreased until it was inactive at day 14 post-ensiling in both TMR silages. During the early stage of fermentation, the main amylase-producing microbes were Bacillus amyloliquefaciens (B. amyloliquefaciens), B. cereus, B. licheniformis, and B. subtilis in ATMR silage and B. flexus, B. licheniformis, and Paenibacillus xylanexedens (P. xylanexedens) in LTMR silage, whereas Enterococcus faecium was closely associated with starch hydrolysis at the later stage of fermentation in both TMR silages. B. amyloliquefaciens, B. licheniformis, and B. subtilis and B. licheniformis, B. pumilus, and P. xylanexedens were the main source of microbial hemicellulase during the early stage of fermentation in ATMR and LTMR silages, respectively. Conclusion The microbial amylase contributes to starch hydrolysis during the ensiling process in both TMR silages, whereas the microbial hemicellulase participates in the hemicellulose degradation only at the early stage of ensiling.